2015
DOI: 10.4103/0189-6725.160364
|View full text |Cite
|
Sign up to set email alerts
|

Neck masses in paediatric population: An experience with children attended the Central Teaching Hospital of Pediatrics in Baghdad 2008-2009

Abstract: Background:Pediatric neck mass is a frequent cause for surgical consultation. Neck masses can be simply classified into congenital, inflammatory, and neoplastic. Although most of the cases are due to benign processes, malignant causes must not be overlooked. The aim of this study is to assess the paediatric neck masses in Iraqi patients highlighting the distribution of cases according to their demographic characteristics and etiology.Patients and Methods:A cross-sectional observed study is conducted in the Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
11
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
(24 reference statements)
7
11
1
1
Order By: Relevance
“…[14][15][16][17] We had 15 cases (10%) of branchial cyst presenting with complaints of slowly growing painless mass in anterior triangle of neck more on left side. Our findings were similar to those by Al-Mayoof and Gov-Ari et al 11,12 Incidence of cystic hygroma and lipoma in our study was 2% which was similar to Showket et al 8 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…[14][15][16][17] We had 15 cases (10%) of branchial cyst presenting with complaints of slowly growing painless mass in anterior triangle of neck more on left side. Our findings were similar to those by Al-Mayoof and Gov-Ari et al 11,12 Incidence of cystic hygroma and lipoma in our study was 2% which was similar to Showket et al 8 …”
Section: Discussionsupporting
confidence: 93%
“…Our findings were similar to the studies by Showkat et al, Lucumay et al, Ingale et al, Al Mayoof et al, Gov-Ari et al [8][9][10][11][12] Suppurative lymphadenopathy was seen in 22 cases (14.7%). They had complaints of rapidly growing neck mass with pain and fever.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, some changes can be observed in the distribution depending to the socio-economic status (15). According to Meier and Grimmer (5) and D'anza (13), the most common pathology is reactive lymphadenopathy following upper respiratory tract infection.…”
Section: Discussionmentioning
confidence: 99%
“…AlMayoof et al found inflammatory category was the main group accounting 57.8%, reactive non-suppurative lymphadenitis 40.6%, then suppurative lymphadenitis 15.6%, followed by the congenital category 25%, thyroglossal duct cyst 9.3%, then branchial cleft anomalies 7.8%, neoplastic 12.5%, and then the noninflammatory non neoplastic 4.7%. 9 Ragesh et al studied neck masses in children in India they found inflammatory category was the main group accounting 54%, tuberculous lymphadenitis 28%, reactive lymph node hyperplasia 20%, and chronic non-specific lymphadenitis 6%, followed by the congenital category 30%,and neoplastic 16%. 10 Lucumay et al studied pediatric neck masses in Northwestern Tanzania they found inflammatory category was the main group accounting 43.9%.…”
Section: Discussionmentioning
confidence: 99%